Pesticides in the distilled spirits of wine and its byproducts - Cabras, P.; Angioni, A.; Garau, V. L.; Minelli, E. V.; Melis, M.; Pirisi, F. M. (Amer Chemical Soc, 1997)
The fate of eight fungicides (benalaxyl, fenarimol, iprodione, metalaxyl, myclobutanil, procymidone, triadimefon, and vinclozolin) and five insecticides (dimethoate, fenthion, methidathion, parathion methyl, and quinalphos) in wine and its byproducts (cake and lees) during the production of distilled spirits was studied. Among the pesticides studied, only fenthion, quinalphos, and vinclozolin residues were present in the distilled spirits. During wine distillation, respectively 13% and 5% of the initial residues of fenthion and vinclozolin were transferred to the distilled spirit. Low percentages (2% for fenthion and 0.1% for vinclozolin) of these active ingredients (AI) also passed from the lees to the final-distilled spirit, when samples were fortified at 10.1 and 26.1 ppm for fenthion and vinclozolin, respectively. Quinalphos passed only from the lees to the final-distilled spirit in percentages lower than 1% when samples were fortified at the highest concentration (4.6 ppm).
Keywords: pesticides; residues; distilled spirits